Dos sentidos da paixão e da esperança no engano: Cartas portuguesas - Prado, Priscila Finger do (2010)
This work aims to analyze the semantic movements in Cartas portuguesas, assigned to Mariana Alcoforado. After the authorial problematic´s presentation in the book, at the introduccion, there is a study´s division in two moments. In the first, it finds to situate the book between the produccion of the baroque period, as well as to delimit aspects of its main theme (the love) and its genre (letter). In the second, it starts with a panoramic lecture of the axis semantics movement in the Cartas, to verify how its appears in each letter. With the sense´s displacement, dominated by Passion and Mistake´s axis, as well as to suggest this work´s title, it realizes a change in writing´s focus, that begins in the loved object, passes to the felling, until arrives in the writing´s recuse, to the peace´s search. With this, it notes that passion moves the writing, in this book.